2019
DOI: 10.1128/aac.00710-19
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Efficacy of MEDI3902 in Pseudomonas aeruginosa Bloodstream Infection and Acute Pneumonia Rabbit Models

Abstract: Pseudomonas aeruginosa is a challenge for clinicians due to increasing drug resistance and dwindling treatment options. We report on the activity of MEDI3902, an antibody targeting type 3 secretion protein PcrV and Psl exopolysaccharide, in rabbit bloodstream and lung infection models. MEDI3902 prophylaxis or treatment was protective in both acute models and exhibited enhanced activity when combined with a subtherapeutic dose of meropenem. These findings further support MEDI3902 for the prevention or treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
(12 reference statements)
0
19
0
Order By: Relevance
“…The resistance rates of PA are increasing in many parts of the world: recent studies reported the widespread presence of extreme drug-resistant (XDR) high-risk clones in healthcare settings [5]. Therefore, several evolving translational strategies are being explored for the control and therapy of PA, including immunotherapy [6], phage therapy [7] and vaccination. Several types of vaccines have been developed and tested in Phases I-III clinical trials [8]; however, currently there is no approved option for use in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance rates of PA are increasing in many parts of the world: recent studies reported the widespread presence of extreme drug-resistant (XDR) high-risk clones in healthcare settings [5]. Therefore, several evolving translational strategies are being explored for the control and therapy of PA, including immunotherapy [6], phage therapy [7] and vaccination. Several types of vaccines have been developed and tested in Phases I-III clinical trials [8]; however, currently there is no approved option for use in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Like the other Hu-mAb from AstraZeneca PLC, this product was also dosed i.v., excluded patients on antibiotics, and only patients positive for P. aeruginosa were enrolled. Multiple animal models led to the development of this Hu-mAb [55,59], and aside from the anti-virulence mechanism of action, it was recently shown in vitro that MEDI3902 can steer neutrophils through a "dead zone" to reach and destroy biofilm generated by P. aeruginosa [60], which highlights another positive aspect of infection remediation.…”
Section: Previous Failures Lead To Current Successmentioning
confidence: 99%
“…Finally, there are some that have said that the efficacy of Hu-mAb therapeutics is not significant enough but, again, this criticism will be addressed in the future as technology improves and more targets are added either via a cocktail or by multivalent antibody engineering. It has already been shown that the addition of just one target with a bispecific antibody improves Hu-mAb efficacy [55,59,60]. Further, there are now pentavalent antibodies and mAb cocktails that are also being explored to improve efficacy [73,74].…”
Section: Future and Conclusionmentioning
confidence: 99%
“…Active immunization with recombinant PcrV also improved acute lung injury and mortality in P. aeruginosa pneumonia models [64][65][66]. In recent years, more researchers have reported the clinical application of anti-PcrV antibodies, which have been developed using different approaches [67][68][69][70].…”
Section: Blocking Effects Of Antibodies Against the Bacterial Type IImentioning
confidence: 99%
“…Antibodies 2019, 8, 52 6 of 13 recent years, more researchers have reported the clinical application of anti-PcrV antibodies, which have been developed using different approaches [67][68][69][70].…”
Section: V-antigen Homologsmentioning
confidence: 99%